Human Capital Available for the Development of the Mining Industry of the Future - Govt policies, companies planning and market trends to achieve a future scenario for the developing of the mining ind. - Establishment of Educational Initiatives - L. Contretras (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
This study has as an objective to analyze and to propose actions to improve the quantity and quality of the graduate education in the area of mining industry, specifically of mining engineers, metallurgists, geologists, to satisfy the expectations of professionals in the mining industry. Included are an analysis of the present scenario and the future demands in countries like Chile and proposed plans for the Establishment of Educational Initiatives, country policies and market forecast, vis-a-vis the experience of Australia, South Africa, United Kingdom, Canada and the United States of America.